PENDIDIKAN ISLAM DI ERA DISRUPSI - Maspuroh, Maspuroh (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Now with the entry of humans into the era of disruption, namely the era of the industrial revolution 4.0, and complemented by the inclusion of fixing after the end of the Covid-19 pandemic, the Islamic education process has undergone very drastic changes. The role of humans is starting to be replaced by computerized systems and artificial intelligence. This study uses a qualitative approach with the library research method (library research). In the era of disruption that is completely confusing with leaps and bounds of changes in social life which results in drastic changes in people's behavior from old age to children in general, it shows a decline in the nation's moral values, including several indicators that the authors note the decline in moral values in children's personalities. This nation includes decreased respect for parents, teachers, and others, decreased empathy, sympathy and lack of respect. The challenges of education in the era of disruption must be able to face developments. The world of education in Indonesia requires various innovations to remain functional and optimal in the midst of undetected changes. The challenges of education are actually faced by all parties, both families, government and society, especially teachers and lecturers who are required to make changes in mindset quickly and exponentially so that they are able to answer and anticipate challenges.